Community and conservation: Sea turtle conservation in Southern Terengganu, Malaysia / Tsuji Shuji - Tsuji , Shuji (2016)
This study is a sociological insight on sea turtle conservation in the State of Terengganu, Malaysia, with special emphasis on community based conservation programme practiced in Kerteh district in the Southern part of the state. Terengganu is known as one of the greatest nesting ground of sea turtles in the Asia-Pacific. Further, the state has a very long history of sea turtle conservation for more than four decades, even though the effort has not necessarily prevented drastic decline of the nesting numbers. In early 2000s, Malaysia’s first community-based wildlife conservation project launched at Ma’daerah Sea Turtle Sanctuary located in Kerteh district. The studyregards conservation projects as a game among stakeholders embedded in a particular context of local economy. It tries to describe actual interest of the stakeholders behind existing conservation programme and how the stakeholders achieved consensus. In this connection, the study meticulously describes the context of local economy to understand why the actors choose a certain option and how the choices resulted in the existing conservation strategy. In the context of the State of Terengganu, the main stakeholders are state government, petrochemical industry, conservation NGOs, fishery administrators, and local fishermen. The existing strategy was adopted under dominant influence of petroleum industry. As a consequence, it failed to mitigate impacts of drastic loss of nesting beaches due to rapid industrialisation of the coastal area of the State. This study also attempts to present voice of underrepresented in a conservation project. Even though local fishermen are crucial stakeholder in sea turtle conservation, no serious assessment has been conducted on how they consider about sea turtle conservation. Lack of sincere inquiry toward fishermen’s own vision led conservationists to a fixed idea as follows: fishermen are too ignorant and greedy to care for environment. Without enlightenment, they would never behave responsibly. This study challenges such assumptions by presenting actual voice of fishermen based on semi-structured interview in fishing villages. Modified Grounded Theory approach was applied to reconfigure the voices of fishermen. The study also identified factors, which would affect fishermen’s behaviour toward sea turtle conservation, using multivariate analyses including Exploratory Factor Analysis, Analysis of Variance, and Path Analysis. This analysis revealed that the sense of crisis against degrading marine environment serves as a strong platform for fishermen’s support for marine conservation. Further, the analysis showed that their civic moral to abide-by given rules trigger guilty feeling against by-captures. These result overrode negative assumption against fishermen’s attitude toward conservation.